Study on The Impact of Gelatin Coating Containing Lactobacillus acidophilus and Lactobacillus reuteri on Chicken Fillets Shelf Life - Kamal, Rohullah; Ahmadzai, Noorullah; Samimi, Sayed Rahman (Indonesian Association of Food Technologists, 2024)
The purpose of this study is to assess how chicken fillet shelf life and sensory evaluation are affected by 1% Gelatin coating containing Lactobacillus acidophilus PTCC 1643 and Lactobacillus reuteri ATCC 1655. Probiotic-containing cultures were introduced straight to the coating solution in this investigation. Measures were taken of the chemical (pH, TVB-N, peroxide value), microbiological (Total viable count (TVC), psychrotrophic count (PTC), Enterobacteriaceae, and Pseudomonas spp.), and sensory properties. During the storage of the chicken fillet, which was kept at 4° C for intervals of 0, 3, 6, 9, and 12 days, the antimicrobial properties of the coating in the groups treated with gelatin, Lactobacillus acidophilus, and Lactobacillus reuteri were significantly (p<0.05) higher than those in the control groups, despite the fact that the results showed the highest chemical properties and sensory score across all parameters. However, gelatin + Lactobacillus reuteri and gelatin + Lactobacillus acidophilus did not differ significantly (p<0.05). Additionally, samples treated with gelatin and probiotics showed no changes in color or texture, but their odor and taste scores decreased. We draw the conclusion that gelatin is an appropriate matrix for probiotic incorporation and long-term fillet storage.